2015
DOI: 10.1093/jpepsy/jsv113
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Examination of Hope and Optimism and Their Role in Type 1 Diabetes in Youths

Abstract: It may be beneficial to assess hope in pediatric T1DM patients to identify youths who may be at risk for poor diabetes management, and to test the benefit of hope-based intervention efforts in clinical studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(23 citation statements)
references
References 37 publications
1
21
1
Order By: Relevance
“…Twenty‐six percent of youth in this sample also had elevated depressive symptoms, which matches recent findings that almost a third of youth with T1DM are expected to report depressive symptoms . Consistent with previous research, glycemic control was associated with adherence, depressive symptoms, and hope . Children with greater depressive symptoms demonstrated worse glycemic control, but hope and BOLUS were 2 protective factors that suggest further investigation in longitudinal samples to determine if they are mediators of the relationship between depression and HbA1c.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Twenty‐six percent of youth in this sample also had elevated depressive symptoms, which matches recent findings that almost a third of youth with T1DM are expected to report depressive symptoms . Consistent with previous research, glycemic control was associated with adherence, depressive symptoms, and hope . Children with greater depressive symptoms demonstrated worse glycemic control, but hope and BOLUS were 2 protective factors that suggest further investigation in longitudinal samples to determine if they are mediators of the relationship between depression and HbA1c.…”
Section: Discussionsupporting
confidence: 88%
“…For instance, children with poor glycemic control may check blood glucose frequently due to frequent highs/lows without treating, while appropriate insulin dosing before meals more directly influences glycemia. Interestingly, BOLUS did not impact the cross‐sectional relationship between hope and glycemic control, although adherence as measured by BGM was found to mediate this relationship by Van Allen et al This discrepancy may be due to differences in the amount of variability in individual BOLUS scores vs BGM, and requires further research using independent samples. Alternatively, the relationship between hope and glycemic control may be better explained by factors that were not the focus of this study, such as self‐efficacy, optimism, perceived social support, parenting strategies, or general well‐being …”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Emerging evidence has demonstrated that increased hope may be a protective factor in QOL for those facing medical challenges (Barnum et al, ; Berg et al, ; Maikranz et al, ; Santos et al, ; Van Allen, Seegan et al, ; Van Allen, Steele et al ). However, contrary to past research, and to study hypotheses, findings indicated that hope did not significantly predict concurrent QOL in our sample.…”
Section: Discussionmentioning
confidence: 99%